PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, KEPEMILIKAN SAHAM PUBLIK, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2015 - Desiana Indriyawati, 13.05.52.0062; Poerwati, Tjahjaning (Students' Journal of Accounting and Banking, 2017)
This study aims to examine the effect of leverage, liquidity, profitability, public stock ownership, company size and age of the company on the disclosure of the completeness of financial statements of companies listed on the IDX period 2013-2015. The population in this study are companies listed on the Indonesia Stock Exchange during the period 2013-2015. Sampling in this study using purposive sampling method, so that the number of companies included in the sample criteria as many as 263 companies. Data analysis method used in this research is multiple linear regression analysis. The result of the research shows that leverage variable has positive effect not significant to the completeness of financial statement disclosure. liquidity has no significant negative effect on the completeness of the disclosure of financial statements. Profitability variable has a no significant positive effect on the completeness of financial statement disclosure. The variable of public share ownership has negative effect not significant. The size of the company has a significant negative effect on the completeness of the disclosure of financial statements. Company age variable have positive effect not significant to completeness of financial statement disclosure.Keywords: Disclosure of Financial Statement Completion, Leverage, Liquidity, Profitability, Public Ownership of Shares, Company Size, Age of Company